Trys šimtai metų Vilniaus akademijos leidiniui: Jokūbas Benetis „Virtus dexterae domini“..., 1674 m. - Kazlauskas, Benediktas (Knygotyra, 1974)
The present paper consists of three parts: the literary and historical analysis of the poem, the translation of the poem into Lithuanian and the glossary.After a short introduction which deals with the humanistic Latin literature, popular in Lithuania in the 16–17th centuries the paper presents some basic facts about the author of the poem, a nobleman of English extraction, a student of Vilnius Academy, who wrote a poem in Latin and published it in Vilnius in 1674 under the title “The Might of Lord’s Right Hand” (Virtus Dexterae Domini) in glory of the battle at Khotin. The battle was directed by the Lithuanian Army commander Mykolas Kazimieras Pacas and the vice chancellor Mykolas Kazimieras Radvila. The Polish army faught under the leadership of the commander−in−chief marshal Jan Sobieski. The paper reviews the political situation of the Great Lithuanian Principality and the relations it maintained with its neighbours. On the basis of this the present paper rejects the opinion of some historians who hold that the Lithuanian Army did not at all participate in the battle at Khotin in 1673.The poem comprises 743 hexameter lines. It has not been translated into Lithuanian and has not been so far subjected to literary analysis. The supplemented translation is effected by the author of the present paper. The poem reflects the fight conducted by the Great Principality against the Turks and greatly supplements our knowledge about the battle of Khotin. The poem glorifies Lithuania and her leaders, it possesses a lasting historical panegyrical and literary value.The glossary seeks to explicate the names and the place-names which occur in the poem.